Variabel Akuntansi dan Non Akuntansi sebagai Determinan Transfer Pricing - Sembiring, Christofer; Kuntadi, Cris (Universitas Katolik Soegijapranata, Semarang, 2024)
Transfer pricing refers to a company's policy for calculating the transferred price of a transaction with a related party. Even though it is actually neutral, the terminology of transfer pricing is more often used to explain the practice of reducing the tax burden by transferring company profits to other companies within the same group. The purpose of this study is to compare the results of previous research on transfer pricing in Indonesia and provide recommendations for future transfer pricing research agendas. This study used a qualitative method with a literature review approach. The data source is in the form of 44 research results published between 2019 until May 2023 from journals that have been accredited by SINTA. Based on the results of previous research, variables that influence transfer pricing are identified, namely accounting variables (tax, exchange rate, profitability) and non-accounting variables (good corporate governance, foreign ownership, tax haven)